Autologous Transplantation of Bone Marrow Adult Stem Cells for the Treatment of Idiopathic Dilated Cardiomyopathy - Westphal,Ricardo João (2014)
Background:Morbimortality in patients with dilated idiopathic cardiomyopathy is high, even under optimal medical treatment. Autologous infusion of bone marrow adult stem cells has shown promising preliminary results in these patients.Objective:Determine the effectiveness of autologous transplantation of bone marrow adult stem cells on systolic and diastolic left ventricular function, and on the degree of mitral regurgitation in patients with dilated idiopathic cardiomyopathy in functional classes NYHA II and III.Methods:We administered 4,54 x 108 ± 0,89 x 108 bone marrow adult stem cells into the coronary arteries of 24 patients with dilated idiopathic cardiomyopathy in functional classes NYHA II and III. Changes in functional class, systolic and diastolic left ventricular function and degree of mitral regurgitation were assessed after 3 months, 6 months and 1 year.Results:During follow-up, six patients (25%) improved functional class and eight (33.3%) kept stable. Left ventricular ejection fraction improved 8.9%, 9.7% e 13.6%, after 3, 6 and 12 months (p = 0.024; 0.017 and 0.018), respectively. There were no significant changes neither in diastolic left ventricular function nor in mitral regurgitation degree. A combined cardiac resynchronization and implantable cardioversion defibrillation was implanted in two patients (8.3%). Four patients (16.6%) had sudden death and four patients died due to terminal cardiac failure. Average survival of these eight patients was 2.6 years.Conclusion:Intracoronary infusion of bone marrow adult stem cells was associated with an improvement or stabilization of functional class and an improvement in left ventricular ejection fraction, suggesting the efficacy of this intervention. There were no significant changes neither in left ventricular diastolic function nor in the degree of mitral regurgitation.